Functional Dissection of Auxin Response Factors in Regulating Tomato Leaf Shape Development - Wu, Lingjie; Tian, Zhendong; Zhang, Junhong (Frontiers in Plant Science, 2018)
The phytohormone auxin is involved in many aspects of plant growth and developmental processes. The tomato Aux/IAA transcription factor SlIAA9/ENTIRE/E plays an important role in leaf morphogenesis and fruit development, and the E gene encodes a protein from the Aux/IAA family of auxin response repressors. Both SlIAA9-RNAi transgenic and entire (e) mutant plants reduce the leaf complexity in tomato, but the underlying mechanism is not yet completely resolved. Auxin signaling is known to regulate target genes expression via Aux/IAA and ARFs (Auxin Response Factors) transcriptional regulators. ARFs mediate a wide range of developmental processes. Through an Y2H (Yeast Two-Hybrid) assay coupled with expression profiling of the SlARF genes family, we identified a group of ARFs: SlARF6A, SlARF8A, SlARF8B, and SlARF24. Pull-down and BiFC (Bimolecular Fluorescence Complementation) results demonstrated that these SlARFs interact with SlIAA9 in vitro and in vivo, and the e mutation altered the expression patterns of multiple SlARFs. The simple leaves of the e mutant were partially converted to wild-type compound leaves by VIGS (virus-induced gene silencing) of these four SlARFs. Furthermore, IAA content in these samples was significantly increased compared to the e mutant. In addition, SlARF6A and SlARF24 bound to the SlPIN1 promoter and act as transcriptional activators to regulate genes expression involved in leaflet initiation. It may also suggest that SlARFs regulate leaf morphology through direct binding to auxin-responsive genes in the absence of SlIAA9, providing an insight for the role of SlARFs in leaf shape development.